Association between mothers’ problematic Internet use and maternal recognition of child abuse - Sakakihara, Aya; Haga, Chiyori; Kinjo, Aya; Osaki, Yoneatsu (Child Abuse & Neglect, 2019)
There are few studies about mothers’ problematic Internet use (PIU). Mothers’ PIU may lead to inadequate parenting and child abuse. This cross-sectional study aimed to clarify the association between mothers’ PIU and their recognition of child abuse. We analyzed data collected of health examinations of children aged 4 months, 1.5 years, and 3 years which were carried out in Matsue City, Shimane Prefecture, Japan between April 2016 and March 2017. The number of the subjects were 1685, 1729, 1674, respectively. We used logistic regression analysis to clarify the association between mothers’ PIU (Young’s Diagnostic Questionnaire for Internet Addiction score: ≥5) and their recognition of child abuse (selecting < True of me > for < I sometimes think that I am abusing my child > on a questionnaire survey), which was adjusted for covariates such as maternal age, number of children, daytime caretaker, social support, postpartum depression, and current smoking status of the parents. Based on the multivariate logistic regression analysis, the mothers’ PIU was significantly correlated with their recognition of child abuse for children aged 4 months, 1.5 years, or 3 years [odds ratio (OR): 13.30, 95% confidence interval (CI): 1.26–139.98, OR: 7.02, 95% CI: 1.28–38.55, and OR: 28.06, 2.48–317.93, respectively]. This study revealed the possibility that mothers with PIU recognize child abuse more than mothers without PIU. However, further studies should be conducted to increase reliability and validity.